2018
DOI: 10.1177/2050640617717158
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of direct anti‐viral agent treatment schedule: Focus on HCV genotype 3

Abstract: Background and aim: Direct antiviral agents (DAAs) have led to high sustained virological responses (SVR) in hepatitis C virus (HCV) patients. However, genotype 3 patients respond to treatment in a suboptimal way. This study aims to identify which of the several treatment schedules recommended for genotype 3 would constitute the best option. Methods: Twenty-four Italian centers were involved in this real-life study of HCV genotype 3 patients treated with DAAs. To expand the number of cases, we conducted a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…First, as regards SOF + RBV regimen, the meta-analysis by Bayatpoor et al [33] reported pooled SVR12 rates on genotypes 2 and 3 at 92% and 55–81% (this depended on treatment duration), respectively, which were lower compared to our analysis for genotype 6 at 100% SVR12 rate. In addition, the meta-analysis by Morisco et al [34] also reported a lower pooled SVR12 rate on genotype 3 at 79%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, as regards SOF + RBV regimen, the meta-analysis by Bayatpoor et al [33] reported pooled SVR12 rates on genotypes 2 and 3 at 92% and 55–81% (this depended on treatment duration), respectively, which were lower compared to our analysis for genotype 6 at 100% SVR12 rate. In addition, the meta-analysis by Morisco et al [34] also reported a lower pooled SVR12 rate on genotype 3 at 79%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, regarding the efficacy of SOF/LDV ± RBV regimen, the meta-analysis by Morisco et al [34] reported pooled SVR12 rate at 83.7% for SOF/LDV on genotype 3. In addition, several meta-analyses [3741] reported pooled SVR12 rates ranging from 95–99.7% of SOF/LDV ± RBV on genotype 1.…”
Section: Discussionmentioning
confidence: 99%